ANALYSIS OF THE RELATIONSHIP OF COMPETITIVENESS AND SUSTAINABLE DEVELOPMENT GOALS - Aleksandra Tošović-Stevanović (PEOPLE: International Journal of Social Sciences, 2025)
In the conditions of the global challenges that surround us at the economic and ecological level, which are very often very different and complex, and very often with a pronounced negative effect on the realization of sustainability goals, it is of great importance to deal with the analysis of the economic dimensions of sustainable development and globalization in order to better understand and realize the global goals of sustainable development. Analyzing the economic development, social inclusion and sustainable environment, as key elements for this research and very important in the context of sustainability approach and their effect on developed and developing countries, the main purpose of this paper is to determine the direction of the relationship of competitiveness and sustainable development which have an impact on global changes. The subject of the research is to define and to analyze the main socio-environmental and economic problems which are directly or indirectly addressed to the sustainable development goals and to identify the links between the concept of competitiveness and the targets goals of sustainable development which reflect the changing global environment. Because of that we want to analyze the relationship of competitiveness and sustainable development goals with some specific examples which are affecting developed and developing countries and to contribute to the ongoing discourse and provide future discussions on the relations between competitiveness and sustainability.